Cover separation of CFRP strengthened beam-type cantilevers with steel bolt anchorage. (1st February 2018) - Zhang, Dawei; Shi, Haifeng; Zhu, Jihua; Su, Meini; Jin, W.L.
Highlights: Analyze mechanism of concrete cover separation through beam-type cantilever test. Clarify the effect of steel anchorage on the concrete cover separation failure. Propose analytical models considering major anchorage parameters and failure modes. Abstract: Concrete cover separation is one of the premature debonding failure modes commonly observed when strengthening reinforced concrete (RC) beams that use externally bonded fibre-reinforced polymer (EB-FRP) become delaminated. Anchorage systems, which postpone or prevent debonding, have proven to be an effective method to achieve higher levels of FRP utilization. Although researchers have widely acknowledged the efficiency of anchorage systems, the effect of a bottom steel bolt anchorage system on the concrete cover separation strength remains unclear. The related design formulation is still in its initial stage, which limits the practical use of this type of anchorage system for FRP strengthening. In this study, specimens of carbon fibre-reinforced polymer (CFRP) laminate strengthened beam-type cantilevers with bottom steel bolt anchors were designed and tested. The principle design parameters such as the location, the length and the number of anchors were investigated and their effects were discussed based on the test results. Furthermore, an analytical approach considering various failure modes of anchors and cantilevers was presented to predict the concrete cover separation strength of anchored specimens. The test results were then compared to the analytical approach in order to verify reliability and accuracy.